2008
DOI: 10.1016/j.electacta.2008.01.098
|View full text |Cite
|
Sign up to set email alerts
|

Bi2O3 modified cobalt hydroxide as an electrode for alkaline batteries

Abstract: Manganese dioxide electrode shows reversible charge storage capacity, if the charge-discharge process is limited to 0.3e − exchange. Addition of small amount of Bi 2 O 3 to manganese dioxide induces reversibility with an exchange of 2e − /Mn. Nickel hydroxide is known to reversibly exchange 1e− . In spite of isostructural relationship between the cobalt hydroxide, nickel hydroxide and manganese dioxide, cobalt hydroxide does not show any electrochemical activity. Bi 2 O 3 modified cobalt hydroxide electrodes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Cobalt hydroxide (Co(OH) 2 ) materials are attractive on account of their layered structure with large interlayer spacing and their well-defined electrochemical redox activity . Being an important electrochemical active material, a great deal of interest has been centered on the utilizations of Co(OH) 2 material in alkaline batteries, fuel cells, and supercapacitors. Previous reports have shown that the film of Co(OH) 2 material has a higher specific capacitance than that of RuO 2 . , Taking into account the high specific area of graphene (theoretically 2630 m 2 ·g −1 ), which can serve as excellent building blocks for nanocomposites, , and the fact that graphene is a promising supercapacitor electrode material, consistently giving good electrochemical performance in strong alkaline electrolytes, the combination of Co(OH) 2 and graphene may produce synergistic results, giving the overall system enhanced electrochemical properties …”
Section: Introductionmentioning
confidence: 99%
“…Cobalt hydroxide (Co(OH) 2 ) materials are attractive on account of their layered structure with large interlayer spacing and their well-defined electrochemical redox activity . Being an important electrochemical active material, a great deal of interest has been centered on the utilizations of Co(OH) 2 material in alkaline batteries, fuel cells, and supercapacitors. Previous reports have shown that the film of Co(OH) 2 material has a higher specific capacitance than that of RuO 2 . , Taking into account the high specific area of graphene (theoretically 2630 m 2 ·g −1 ), which can serve as excellent building blocks for nanocomposites, , and the fact that graphene is a promising supercapacitor electrode material, consistently giving good electrochemical performance in strong alkaline electrolytes, the combination of Co(OH) 2 and graphene may produce synergistic results, giving the overall system enhanced electrochemical properties …”
Section: Introductionmentioning
confidence: 99%
“…To boost the capacitance, they introduced p ‐phenyleneiamine (PPD) and the capacitance reached 156 F g −1 at −20 °C. However, high‐concentration alkaline media are not suitable for Co(OH) 2 as the reversibility is reduced and because it reacts with Co(OH) 2 , poisoning the active material . Using highly soluble neutral salts together with alkaline electrolytes can be an alternative solution to lower the freezing point, but such investigations are rare.…”
Section: Figurementioning
confidence: 99%
“…However, high-concentration alkaline media are not suitable for Co(OH) 2 as the reversibility is reduced and because it reacts with Co(OH) 2 ,p oisoning the active material. [11] Using highly soluble neutral salts together with alkaline electrolytes can be an alternative solution to lower the freezingp oint, but such investigations are rare.N itrates (LiNO 3 , [12] NaNO 3 [13] )a nd chlorates (NaCl, [14] KCl [15] ) usuallyh ave ah igh solubility,b ut if the device is overcharged, these nitrates and chlorates are anodically not very stable.I tm ay jeopardize the stability of the overall performance.T herefore, Vellacheri et al used an aqueouss olution of Li 2 SO 4 as the electrolyte for the graphene electrode, and the working temperature can reach as low as À20 8C. [16] Alexander and his co-workers added ethylene glycol to a mixture of dissolved sulfates,w hich can remain in the liquid phase down to À30 8C, and used it as an electrolytef or MnO 2 and carbon materials,w ith the capacitance reaching 30 Fg À1 .O nt he other hand, NaClO 4 ,w ith higher solubility and stability under anodic conditions,i sabetter choice.…”
mentioning
confidence: 99%
“…2 Both the morphology and composition of the final product depend on factors such as solution precursors, temperature, applied potential, deposition time, and electrode surface. 2 The use of CoO(OH) has been highlighted due to its application as a magnetic material, 1,6 catalyst, 9,10 a positive electrode in alkaline batteries, [11][12][13][14][15][16] supercapacitors, 8,17 and CO detection. 13,18 It also promotes the electrooxidation of various organic molecules, 5 thereby constituting a sensor for analytes such as hydroquinone, 5 carbohydrates and alcohols 8 , and oxalic acid.…”
Section: Introductionmentioning
confidence: 99%